Crisis Team Management in a Scarce Resource Setting: Angkor Hospital for Children in Siem Reap, Cambodia - Henker, Richard Alynn; Henker, Hiroko; Eng, Hor; O’Donnell, John; Jirativanont, Tachawan (Frontiers in Public Health, 2017)
Introduction A crisis team management (CTM) simulation course was developed by volunteers from Health Volunteers Overseas for physicians and nurses at Angkor Hospital for Children (AHC) in Siem Reap, Cambodia. The framework for the course was adapted from crisis resource management (1, 2), crisis team training (3), and TeamSTEPPs© models (4). The CTM course focused on teaching physicians and nurses on the development of team performance knowledge, skills, and attitudes. Challenges to providing this course at AHC included availability of simulation equipment, cultural differences in learning, and language barriers. The purpose of this project was to evaluate the impact of a CTM simulation course at AHC on attitudes and perceptions of participants on concepts related to team performance. Methods Each of the CTM courses consisted of three lectures, including team performance concepts, communication, and debriefing followed by rotation through four simulation scenarios. The evaluation instrument used to evaluate the AHC CTM course was developed for Cambodian staff at AHC based on TeamSTEPPs© instruments evaluating attitude and perceptions of team performance (5). CTM team performance concepts included in lectures, debriefing sessions, and the evaluation instrument were: team structure, leadership, situation monitoring, mutual support, and communication. The Wilcoxon signed-rank test was used to analyze pre- and post-test paired data from participants in the course. Results Of the 54 participants completing the three CTM courses at AHC, 27 were nurses, 6 were anesthetists, and 21 were physicians. Attitude and perception scores were found to significantly improve (p < 0.05) for team structure, leadership, situation monitoring, and communication. Team performance areas that improved the most were: discussion of team performance, communication, and exchange of information. Conclusion Teaching of non-technical skills can be effective in a setting with scarce resources in a Southeastern Asian country.